Post-independence Malaysian short stories : a portrayal of racially inflicted pain. - Isa, Nor Hashimah; Jusoff, Kamaruzaman (Canadian Academy of Oriental and Occidental Culture, 2010)
This paper addresses pain and its endurance as portrayed in post-independence Malaysian short stories. After independence in 1957, the diverse races were forced to stay together in a young country that was constantly in turmoil of racial dissatisfactions and prejudice. Every race carried with them racial baggage that clouded efforts of togetherness and nation-building. In 1969 Malaysians bear witness to the bloody May 13 racial riot that took many lives and scarred the nation. The stories from 1966 to 1969 reveal poverty, inter-racial conflicts amongst Malaysians as writers reveal the continuous hardship, social and economic deprivation endured by the lower income Malays. Pain and enduring it is portrayed in terms of instances of conflicts experienced by the characters in the stories. The Malay stories Pengabdian [Submission] by Awang Had Salleh (1966) and Gadis Tionghua di Daerah Pendalaman [The Chinese maiden from the remote district] by Zaid Ahmad (1969) focus to conflicts about inter-racial love and Malay poverty. In these stories the Malays or indigenous people experienced pain when they saw their people deprived of the opportunity to develop economically via higher education. They endured the immense pain to a certain extent and retaliated by accusing the Chinese of being manipulators of opportunities in the new nation. They felt their people were deprived and felt intimidated at Chinese’s economic success. The stories depicted anger and prejudice felt by the frustrated Malays towards the other races. In the young nation the ethnic groups suffered the pain of racial dissatisfaction during the early years of independence that blew out of proportion when their economic and social aspirations were constantly not met. There was a lot of suspicion and racial hatred that may have triggered the racial riot of 1969. Nation building in the country continued to be unattainable and blurred by constant turmoil.Keywords: Inter-racial conflicts; instances of conflicts; nation building